2005
DOI: 10.1897/04-253r.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of urea on degradation of terbuthylazine in soil

Abstract: Pesticide and nitrate contamination of soil and groundwater from agriculture is an environmental and public health concern worldwide. The herbicide terbuthylazine (CBET) has replaced atrazine in Italy and in many other countries because the use of the latter has been banned because of its adverse environmental impacts. Unlike atrazine, knowledge about the fate of CBET in soil is still not extensive, especially regarding its transformation products, but recent monitoring data show its occurrence and that of its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 31 publications
4
41
0
2
Order By: Relevance
“…However, further DES mineralization was less favoured by the pres- ence of the fertilizer, as confirmed by the lower mineralization observed (0.8% vs 3%). The latter result is ascribable to the fact that the final part of simazine degradation (cyanuric acid, biuret and urea formation) is due mainly to bacteria which use the metabolites as N sources; consequently the degradation is less favoured in soil treated with an exogenous source of N, like urea, as found in other works (Struthers et al, 1998;Gebendinger and Radosevich, 1999;Strong et al, 2002;Barra Caracciolo et al, 2005a). The presence of the herbicide in combination with urea therefore stimulated the presence of some bacterial populations more than others, as confirmed by different percentages of α-, β, γ-Proteobacteria detected in the microcosms.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…However, further DES mineralization was less favoured by the pres- ence of the fertilizer, as confirmed by the lower mineralization observed (0.8% vs 3%). The latter result is ascribable to the fact that the final part of simazine degradation (cyanuric acid, biuret and urea formation) is due mainly to bacteria which use the metabolites as N sources; consequently the degradation is less favoured in soil treated with an exogenous source of N, like urea, as found in other works (Struthers et al, 1998;Gebendinger and Radosevich, 1999;Strong et al, 2002;Barra Caracciolo et al, 2005a). The presence of the herbicide in combination with urea therefore stimulated the presence of some bacterial populations more than others, as confirmed by different percentages of α-, β, γ-Proteobacteria detected in the microcosms.…”
Section: Discussionmentioning
confidence: 54%
“…Pesticide and metabolite extraction was performed in an Accelerated Solvent Extractor, as reported in detail in previous works (Di Corcia et al, 1999;Barra Caracciolo et al, 2005a).…”
Section: Chemical Analysismentioning
confidence: 99%
“…Its half-life is from 6.1 to 14.2 days (Jursík et al 2013). Terbuthylazine [2-tert-butylamine-4-chloro-6-ethylamine-1,3,5-triazine] is a substance introduced in place of atrazine (Caracciolo et al 2005). It belongs to the group of s-triazine herbicides.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature (Caracciolo et al 2005;Dousset et al 1997;James et al 1998;Jursík et al 2013;Sahid and Teoh 1994;Skrzypczak et al 2007), reports can be found concerning the herbicidal effectiveness or degradation in soil of both studied substances, but only of them used separately. However, there is no information concerning the synergic or additive effect of either of these substances on soil microorganisms, enzymatic activity or the growth and development of plants.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is still a lack of simple, practical and efficient way on how to accelerate the degradation of pesticides in soil. Some researchers have found that fertilization could affect the degradation of pesticide in soil [5][6][7]. However, the studies were less on the influence of chicken manure compost (CM) on the production of DOC and degradation of DDT in soil at home and abroad.…”
Section: Introductionmentioning
confidence: 99%